An Econometric Analysis of Impact of Foreign Direct Investment (FDI) Inflow on GDP in Nepal (Janapriya Journal of Interdisciplinary Studies, 2025)
The study examined the impact of FDI inflows on GDP of Nepal, using OLS model for analyzing relationships between FDI and economic growth. The finding revealed a significantly positive impact of Actual Real FDI on Real GDP of Nepal. FDI plays an important role in guiding economic growth and stimulating development across various sectors. The study utilizes secondary data collected from Nepal Rastra Bank and the Ministry of Industry, Commerce, and Supplies over a 28-year period. The study employed annual data from 1996 to 2023, focusing on the key sectors of FDI inflows—Agriculture, Manufacturing, and Services and their impact on economic growth. Using ARDL model, both short-term and long-term relationship between these variables where examined in study. By the examination of potential relationships between the variables, the ARDL bound testing approach facilitated a thorough evaluation of both short-term dynamics and long-term equilibrium. The empirical findings showed a significant long-run relationship between sectoral FDI inflows and economic growth, measured by RGDP, indicating that an increase in sectoral FDI inflows positively influenced economic growth over the long term. However, the short-run analysis showed mixed results, with sectoral FDI inflows having both positive and negative effects on RGDP growth, depending on the lag structure. The study concluded that while sectoral FDI inflows can be an effective tool for promoting economic growth in Nepal, their impact on GDP requires careful consideration of long-term sustainability and the potential short-term volatility they may introduce across different sectors. Overall, the findings showed a significant relationship between overall FDI inflow and GDP, as well as between inflows sectoral FDI inflows and GDP, highlighting thatboth sector-specific and total FDI inflows have a meaningful impact on overall economic growth of a nation.